2020
DOI: 10.1177/0886260519898438
|View full text |Cite
|
Sign up to set email alerts
|

Domestic Violence Interventions in Social and Health Care Settings: Challenges of Temporary Projects and Short-Term Solutions

Abstract: Social welfare service and health care providers are in a key position to implement successful domestic violence (DV) interventions. However, it is known that DV intervention and prevention work is often lacking in coordination and continuity. In addition, the limited resources, hectic work pace, and changing practices negatively affect the development of successful ways to prevent and intervene in DV. This qualitative study involving 11 focus groups, composed of social welfare and health care professionals ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 40 publications
2
23
0
1
Order By: Relevance
“…It is crucial to be able to bring different professional concerns -health, wellbeing or security -under a shared purpose and interpretation. Many studies have shown the importance of interprofessional or interdisciplinary training in overcoming these kinds of "language barriers", but there is a significant lack of proper DV-related training for many professionals in general (see Husso et al, 2020;Koistinen & Holma, 2015;Minsky-Kelly et al, 2005;Stover & Lent, 2014;Szilassy et al, 2013;Warrener et al, 2013). Without a proper understanding of the many causes and consequences of violence, it can be difficult to get hold of the multiple but separate processes that are concurrently ongoing within the different agencies (Bacchus et al, 2003;Nikupeteri, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It is crucial to be able to bring different professional concerns -health, wellbeing or security -under a shared purpose and interpretation. Many studies have shown the importance of interprofessional or interdisciplinary training in overcoming these kinds of "language barriers", but there is a significant lack of proper DV-related training for many professionals in general (see Husso et al, 2020;Koistinen & Holma, 2015;Minsky-Kelly et al, 2005;Stover & Lent, 2014;Szilassy et al, 2013;Warrener et al, 2013). Without a proper understanding of the many causes and consequences of violence, it can be difficult to get hold of the multiple but separate processes that are concurrently ongoing within the different agencies (Bacchus et al, 2003;Nikupeteri, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Thematic analysis was utilized to approach similarities and differences and to reveal unanticipated insights concerning interprofessional collaboration (Braun & Clarke, 2006). The analysis of the interprofessional collaboration descriptions was based on our research aims to examine both challenges and possibilities in working on DV-related issues in the specific context of interprofessional cooperation, as well as to further develop our previous findings on confronting DV in social and health care settings (see also Husso et al, 2020;Virkki et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations